Factores Socioculturales Que Interfieren En La Realización Del Papanicolaou En Mujeres Indígenas Mexicanas - Zapata, Francisca Velasco; Miranda de la Cruz, Armando; Magaña-Olán, Lorena; Hernández, Janett Marina García; Madrigal, Jairo David Contrera (European Scientific Journal, ESJ, 2018)
Introduction: Papanicolaou test was introduced in 1943 by the Dr. George Papanicolaou as an examination of early detection for the Cancer Cérvico Uterino (CACU), it is the most frequent test of detection in women who do not have symptoms. It is the most common second type of cancer in women, of the different types of cancer that they affect the women in reproductive present age in developing countries, rural populations and indigenous zones. I target: to identify the sociocultural factors that they interfere in the accomplishment of the Papanicolaou in wives of a community indigenous to Saint Thomas of Tenosique municipality of Pino Suárez, Tabasco. Methodology: Quantitative descriptive, market investigation across the sampling not probabilistic for incidental convenience with one n = 23 women with ages between 25 and 35 alive years sexual activates. Results: Results: it predominated over the item of age between 29 and 35 years; the level of education that prevails is the primary one, for the marital status the majority is in free union and up to the moment it has had 2 sexual pairs in his life; the beginning of sexual active life that prevails is 16 to 20 years, and the Papanicolaou has never been realized by motives of lack of interest, by the influence of the pair and for not knowing the purpose of there being realized the procedure of periodic form. Conclusion: This study demonstrates that the women have an indifferent attitude towards Papanicolaou capture; since 83.3% of the women presents this attitude, of equal way 70.8 % agrees very in that there is important the opinion of his pair the test to take.